Fundamental gap in fundamental biology - Kordium, V.A.; Andrienko, V.I.; Maslova, O.A.; Shuvalova, N.S.; Irodov, D.M.; Ruban, T.A.; Sukhorada, E.M.; Likhacheva, L.I.; Shpilevaya, S.P. (Вiopolymers and Cell, 2011)
The article raises the problems of intracellular spatial and temporal organization of metabolism, signaling, and energy supply of these processes. To provide cell functions, the enzymes of metabolic chains, molecules of signaling pathways, and macroergs (as units of molecular interactions, accompanied by energy consumption) should find their partners and get their precise spatial relationship. The current views are based on ideas of compartmentalization of all processes as local sites of cellular matrix membrane, where specific stages of different metabolic cycles take place. The assembly of complexes of macromolecules in the number and combinations, required for their adequate functioning in the space of a cell, is generally described as intracellular transport of vesicles, implemented by mobile elements of cytoske- leton. Inside the vesicle there is «effective load» – macromolecules. The membranes of these vesicles fuse with specific sites of the matrix membranes and therefore relocate macromolecules. Neither calcula- tions nor assumptions allow explaining precise formation of enzymatic chains, their interaction, signaling, etc. on this basis. Such transport of macromolecules (inside vesicles) enables solving other tasks. The concept of search-and-address systems in the form of space-scanning micro vesicles is proposed and well-grounded for purposes of searching for partners, forming chains and complexes, and building compartments. The micro vesicles collect corresponding chains of enzymes, signaling, and ensure the interactions on their surface. These micro vesicles are exactly those compartments, which provide for both precision of processes and their relationship. Keywords: metabolism, cell, compartmentalization, vesicle, trans- port of macromolecules, precision of processes.